2019
DOI: 10.1038/s41598-019-44123-4
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-related deterioration of intercellular junctions in the peritoneal mesothelium promotes the transmesothelial invasion of ovarian cancer cells

Abstract: Mechanisms of transmesothelial invasion of ovarian cancer are still poorly understood. Here we examined whether this phenomenon may be determined by an expression of intercellular junctions in peritoneal mesothelial cells (PMCs). Analysis of ovarian tumors showed that cancer cells are localized below an intact layer of PMCs. The PMCs located near the invaded cancer cells displayed low expression of connexin 43, E-cadherin, occludin, and desmoglein, as well as expressed SA-β-Gal, a marker of senescence. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Cx43 expression on membranes mediates the effective signal transduction from extracellular to intracellular. Numerous studies have reported that the NF-κB signaling pathway involves a variety of inflammatory processes that can interact with Cx43 (29,30). Moreover, the NF-κB signaling pathway is also reported to play a key role in regulating the expression of adhesion-related molecules, including ICAM-1 and VCAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 expression on membranes mediates the effective signal transduction from extracellular to intracellular. Numerous studies have reported that the NF-κB signaling pathway involves a variety of inflammatory processes that can interact with Cx43 (29,30). Moreover, the NF-κB signaling pathway is also reported to play a key role in regulating the expression of adhesion-related molecules, including ICAM-1 and VCAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…MCs, which are mesodermal in origin and possess both epithelial and mesenchymal features, are linked by several types of intercellular junctions, including tight junctions (TJs), adherens junctions, desmosomes and gap junctions ( Kastelein et al, 2019 ). SOC cells may disrupt the intercellular junctions within the MCs, favouring transmigration through the mesothelial monolayer ( Pakula et al, 2019a ). In this context, during the metastasis process, a subset of MCs undergoes a mesothelial-to-mesenchymal transition (MMT), a complex and step-wise process that begins with alterations in cellular architecture and include a deep molecular reprogramming with new biochemical instructions ( Pakula et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown changes in connexin gene expression in response to immortalization [ 108 , 109 , 110 ] but have not investigated the underlying mechanism of connexin function in this situation. A decrease in GJIC with age and with senescence has also been reported [ 111 , 112 , 113 , 114 ], as well as changes in connexin expression during senescence [ 115 ]. In the context of untransformed cells, knockdown of Cx43 in glomerular mesangial cells increased senescence-associated β-galactosidase staining [ 116 ], and Cx43 gene knockout in mesenchymal stem cells also increased cellular senescence.…”
Section: Mechanistic Roles Of Connexins In the Major Cancer Phenotmentioning
confidence: 95%